Prevalence of pre-diabetes and diabetes mellitus in Polycystic Ovarian Syndrome (PCOS) - Ullah, Habib; Noor, Kalsoom; Aziz, Abdul (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine prevalence of pre-diabetes and diabetes mellitus in polycystic ovarian syndrome (PCOS) Study Design: Cross sectional study. Non probability consecutive sampling was done. Sample Size: The estimated sample size was 84 women with 95% confidence level and confidence limit of ±5%. Setting: Outpatient departments of Medicine and Gynaecology & Obstetrics at a tertiary care hospital of Quetta, Pakistan. Period: January 2021 to October 2021. Methodology: All women of age 18-40 years who fulfilled the Rotterdam criteria of PCOS were included. Those having fasting blood sugar (FBS) ≥126mg/dl or 2 hour blood sugar > 200 mg/dl on OGTT were said to have diabetes mellitus. Those having FBS between 100-125 mg/dl were said to have impaired fasting glucose (IFG) and those having 2 hour blood sugar between 141-199 mg/dl were said to have impaired glucose tolerance (IGT). Their age, BMI and Oral glucose tolerance test (OGTT) results were documented in the proforma. For analysis SPSS version 20 was used. Results: The mean age in our study was 29.12 ± 6.39 years and mean BMI was 30.49 ± 4.83 kg/m2. A screening OGTT revealed that 7.1 % of PCOS individuals have type 2 diabetes mellitus and 30.9 % had pre-diabetes (IFG, IGT). Conclusion: The prevalence of pre-diabetes and diabetes is high in PCOS, the main risk factor is increased BMI. Prevention and education should be undertaken in such individuals to avoid future complications.